Hematopoietic stem cell a reservoir of innate immune memory - Lucas Ruffinatto; Yann Groult; Johanna Iacono; Sandrine Sarrazin; Bérengère de Laval (Frontiers in Immunology)
Hematopoietic stem cells (HSCs) are a rare, long-lived and multipotent population that give rise to majority of blood cells and some tissue-resident immune cells. There is growing evidence that inflammatory stimuli can trigger persistent reprogramming in HSCs that enhances or inhibits the cellular functions of these HSCs and their progeny in response to subsequent infections. This newly discovered property makes HSCs a reservoir for innate immune memory. The molecular mechanisms underlying innate immune memory in HSCs are similar to those observed in innate immune cells, although their full elucidation is still pending. In this review, we examine the current state of knowledge on how an inflammatory response leads to reprogramming of HSCs. Understanding the full spectrum of consequences of reshaping early hematopoiesis is critical for assessing the potential benefits and risks under physiological and pathological conditions.